Pengaruh Manajemen Laba, Thin Capitalization dan Arus Kas Operasi terhadap Penghindaran Pajak - Riani, Anisa; Romadhina, Anggun Putri (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2026)
This study aims to analyze the effect of earnings management, thin capitalization, and operating cash flow on tax avoidance in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This study uses secondary data in the form of annual financial reports obtained from the official IDX website. The sampling technique used was purposive sampling, with a sample size of 21 companies, resulting in 105 observations over the five years of the study. The independent variables in this study consist of earnings management (X1), thin capitalization (X2), and operating cash flow (X3), while the dependent variable is tax avoidance (Y). The analytical method used is panel data regression with the help of EViews 13 software, and the results of the model selection test indicate that the Random Effect Model (REM) is the most appropriate model. The results show that partially earnings management and operating cash flow did not have effect on tax avoidance, while thin capitalization did. However, simultaneously earnings management, thin capitalization, and operating cash flow had effect on tax avoidance.